THE DRAMATIC ELEMENT CONCEPTS OF TONGGO RAJA – INDONESIA'S TRADITIONAL MUSIC FESTIVAL - Sihite, Jubilezer; Pasaribu, Tiara Kristina; Lestari, Febrika Dwi; Sidabutar, Usman (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2023)
This study aims to reveal the dramatic element concepts of Tonggo Raja, Indonesia’s traditional music festival, which was officially released by the Ministry of Education, Culture, Research and Technology in 2021. It is interesting to investigate performance in traditional musical drama. In this research, the writer applied a descriptive qualitative design with the concept of a dramaturgy approach. The data was collected by watching the YouTube video, interviewing the composer, and transcribing the data. Then, the data are classified into the types of elements they belong to. After obtaining the results of the analysis, they are displayed in a table with description and narration. The results showed that not all ten drama elements of are contained in the performance, including character and conflict. Even though not all the elements were found in the plays, Tonggo Raja has its characteristics, forms, and concepts according to the culture in which it exists. Tonggo Raja is not tied to a particular structure or element, nor does it follow the standard dramaturgical concepts. but the set of activities in the performance form the performance’s elements.